The positioning of palliative care in acute care: A multiperspective qualitative study in the context of metastatic melanoma. Issue 3 (12th October 2015) - Fox, Jennifer; Windsor, Carol; Connell, Shirley; Yates, Patsy
Abstract: Objective: The positioning and meaning of palliative care within the healthcare system lacks clarity which adds a level of complexity to the process of transition to palliative care. This study explores the transition to the palliative care process in the acute care context of metastatic melanoma. Method: A theoretical framework drawing on interpretive and critical traditions informs this research. The pragmatism of symbolic interactionism and the critical theory of Habermas brought a broad orientation to the research. Integration of the theoretical framework and grounded-theory methods facilitated data generation and analysis of 29 interviews with patients, family carers, and healthcare professionals. Results: The key analytical findings depict a scope of palliative care that was uncertain for users of the system and for those working within the system. Becoming "palliative" is not a defined event; nor is there unanimity around referral to a palliative care service. As such, ambiguity and tension contribute to the difficulties involved in negotiating the transition to palliative care. Significance of Results: Our findings point to uncertainty around the scopes of practice in the transition to palliative care. The challenge in the transition process lies in achieving greater coherency of care within an increasingly specialized healthcare system. The findings may not only inform those within a metastatic melanoma context but may contribute more broadly to palliative practices within the acute care setting.